2021
DOI: 10.3390/catal11050538
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Rate-Determining Step of Rh Catalyzed CO2 Reduction: Insight on the Hydrogen Assisted Molecular Dissociation

Abstract: In the context of climate change mitigation, CO2 methanation is an important option for the production of synthetic carbon-neutral fuels and for atmospheric CO2 recycling. While being highly exothermic, this reaction is kinetically unfavorable, requiring a catalyst to be efficiently activated. Recently Rh nanoparticles gained attention as effective photocatalyst, but the rate-determining step of this reaction on Rh surface has not been characterized yet. In this work, Density Functional Theory and Nudged Elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The goal of this work is to rationalize the reaction selectivity toward CH 4 in the case of a photocatalytic process, as observed experimentally. 76 In order to accomplish that, we focused on the understanding of three main aspects: (i) the mechanism and nature of charge injection into CHO moiety, the reaction intermediate of the rate-determining step: 99 dissociation of C−H or C−O bond in CHO leads to carbon monoxide or methane, respectively; (ii) the fate of oxygen and hydrogen atoms along the plasmon-assisted photoinduced hotcarrier dynamics; and (iii) the role of the environment in terms of pure electronic dephasing in the time propagation. In order to accomplish that, we analyzed the results in terms of fieldfree polarization of the system, of the hot-carrier dynamics in the QM portion alone, and in the whole multiscale system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this work is to rationalize the reaction selectivity toward CH 4 in the case of a photocatalytic process, as observed experimentally. 76 In order to accomplish that, we focused on the understanding of three main aspects: (i) the mechanism and nature of charge injection into CHO moiety, the reaction intermediate of the rate-determining step: 99 dissociation of C−H or C−O bond in CHO leads to carbon monoxide or methane, respectively; (ii) the fate of oxygen and hydrogen atoms along the plasmon-assisted photoinduced hotcarrier dynamics; and (iii) the role of the environment in terms of pure electronic dephasing in the time propagation. In order to accomplish that, we analyzed the results in terms of fieldfree polarization of the system, of the hot-carrier dynamics in the QM portion alone, and in the whole multiscale system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Above the cut, at the atomic interlayer distance, an atomistic Rh 19 cluster is set, mimicking the vertex itself as shown in panel (a) of Figure . Adsorbed to the cluster is a CHO fragment, being the CHO dissociation into CH + O the rate-determining step in the thermally activated reaction toward CH 4 . , The atomistic portion of the composite system has been described at the QM level, while a classical polarizable continuum model (PCM) has been used for the large remaining part of the NP. QM calculations are based on DFT, GW, and BSE.…”
Section: Resultsmentioning
confidence: 99%
“…Using a photocatalyst with high HC production rates and low affinity toward CO could therefore bring major improvements to the efficiency and sustainability of steam reforming processes. Conversely, for CO 2 reduction, a photocatalyst with high CO affinity led to high reaction yields and selectivity toward reduction to CH 4 . , Our evidence suggests that CO activation could be partially enhanced by excitation of C–O vibrational motion which, although weaker than the desorption motion, is still present.…”
mentioning
confidence: 79%
“…In addition, Solymosi et al. concluded that the adsorbed CO* could undergo dissociation to a limited extent on a supported Rh catalyst above 473 K at high pressures, which was attributed to the influence of the support. , Under hydrogenating conditions, the adsorbed CO* can either desorb to the gas phase, with the remaining O* species being hydrogenated to water to complete the cycle for the reverse water–gas shift (RWGS) mechanism, or interact with co-adsorbed H* to form intermediate complexes . Jacquemin et al concluded that adsorbed CO 2 can undergo dissociation on a Rh/γ-Al 2 O 3 catalyst, with subsequent reaction of CO* with H 2 , as revealed by in situ DRIFTS experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Karelovic and Ruiz studied the reaction mechanisms for CO 2 hydrogenation over the supported Rh catalysts at low temperatures and proposed that CO is an important intermediate, with the CO* dissociation barrier being comparable to that of the overall reaction. , Recently, several theoretical studies of the reaction mechanism for Rh-catalyzed CO 2 methanation have been published; Kwon and co-workers applied DFT techniques to study the reaction pathways for CO 2 hydrogenation on Rh(111), demonstrating that Rh can facilitate the direct dissociation of CO 2 and that the lowest-energy reaction pathway for CO* hydrogenation to methane was via the formation and dissociation of HCO*, with HCOH* formation and dissociation as a plausible alternative. Similarly, DFT calculations were used to investigate the rate-determining step for CO 2 methanation on the Rh(100) surface, which showed that hydrogen can assist the dissociation of CO*, via hydrogenation to CHO* and its subsequent dissociation to CH* and O* . In addition, ab initio molecular dynamics was applied to study CO activation on Rh surfaces and concluded that CO* more readily undergoes hydrogenation than dissociation .…”
Section: Introductionmentioning
confidence: 99%